Simulation Analysis of Issues with Grid Disturbance for a Photovoltaic Powered Virtual Synchronous Machine - Takahiro Takamatsu; Takashi Oozeki; Dai Orihara; Hiroshi Kikusato; Jun Hashimoto; Kenji Otani; Takahiro Matsuura; Satoshi Miyazaki; Hiromu Hamada; Teru Miyazaki (Energies, 2022)
The increase in inverter-based resources associated with the increased installation of PV sources is a concern because it reduces the inertia of the power system during peak PV generation periods. As a countermeasure to reduce grid inertia, the addition of pseudo-inertia using virtual synchronous machines can be selected, and PV generation can cooperatively contribute to the stable operation of the power system by using the suppressed output as reserve power. However, few studies have analyzed VSMs that do not use batteries and use PV as a resource (PV-VSM) in simulations, including grid interconnection and solar radiation fluctuations, and it is necessary to clarify the issues and discuss countermeasures. In this study, electromagnetic transient response analysis was applied to a VSM connected to a two-generator system, simulations were performed, and the following findings were reported and countermeasure methods for the problem were proposed. When the PV capacity is insufficient for the output required by the VSM inverter, the PV-VSM control system may become unstable. This is caused by a drop in the capacitor voltage of the DC/DC converter due to insufficient PV output. The limiter control system is designed to address this problem by combining the headroom estimation system with the current limiting algorithm. The proposed limiter control system is validated on solar radiation ramp fluctuations as a test case and found that the system was effective in supressing PV-VSM instability. In our simulation case, the PV-VSM with our limiter control can continue to operate stably even if the PV available power is 0.03 [p.u.] short of the inverter’s reference power by the solar power ramp fluctuation, as long as the inverter installation rate is less than 50%.